INFLUENCE OF COATING LAYER TO REDUCE THERMAL STRESSES IN CYLINDRICALLY FORMED METAL MATRIX COMPOSITES - Okumus, Fuat; Turgut, Aydin; Sancaktar, Erol (American Society of Mechanical Engineers (ASME), 2000)
In this study, the use of coating layers is investigated to reduce thermal stresses in the metal matrix composites which have a mismatch in coefficients of thermal expansions in fiber and matrix components. The thermoelastic solutions are obtained based on a three-cylinder model. It is shown that the effectiveness of the layer can be defined by the product of its coefficient of thermal expansion and thickness. Consequently, a compensating layer with a sufficiently high coefficient of thermal expansion can reduce the thermal stresses in the metal matrix. The study is based on a concentric three cylinder model isolating individual steel fibers surrounded with a coating layer and an aluminum matrix layer. Only monotonic cooling is studied. Copyright © 2000 by ASME.
ASME 2000 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, IDETC-CIE 2000 -- 10 September 2000 through 13 September 2000 -- Baltimore -- 186543
Keywords: Aluminum coated steel; Aluminum coatings; Cylinders (shapes); Fiber optic sensors; Metallic matrix composites; Steel fibers; Thermal stress; Aluminium matrix; Coating layer; Coefficient-of-thermal expansion; Cylinder model; In-fiber components; Matrix components; Matrix composite; Matrix layers; Metal matrix; Thermoelastics; Thermal expansion